Pseudo-John Chrysostom"s Homily On Susanna (CPG 4567) (Daniel 13 LXX): Masculinity, psychic typology and the construction of early Christian salvation history - De Wet, Chris L. (HTS teologiese studies, 2021)
This article investigates a short Greek Christian homily, from the 4th century CE, by an anonymous Cappadocian preacher on the narrative of Susanna in Dan 13 LXX. The homily is simply titled, On Susanna (CPG 4567), and has been erroneously transmitted as a work of John Chrysostom. The purpose of this article is to examine more closely the construction of Susanna in the homily, with specific reference to the use of masculinity, psychic typology and finally, the construction of early Christian salvation history. After addressing, in brief, some matters of canonicity, a close reading of On Susanna is given. It is demonstrated that the Cappadocian strategically constructs Susanna like a virginal Christian martyr and ascetic, with the aim of highlighting her masculine steadfastness and dominance in her contest (agōn) against the elders. A significant second move that is made in the homily is to position the masculine Susanna as a type for the soul of the individual, which should also be guarded against the onslaught of sin and the passions.Contribution: This Christian reconstruction of Susanna brings the subjectivity of the individual listener in the audience, and the character of Susanna, in close proximity to one another. In effect, by internalising the narrative of Susanna into the realm of the soul, the anonymous Cappadocian preacher is able to utilise a layered biblical salvation history that incorporates not only narratives from the Bible, but also the audience member’s own individual narrative and struggles into the grander scheme of salvation history.